A glycosylated Fc‐fused glucagon‐like peptide‐1 receptor agonist exhibits equivalent glucose lowering to but fewer gastrointestinal side effects than dulaglutide. Issue 8 (3rd June 2020) - An, In Bok; Byun, Mi Sun; Yang, Sang In; Choi, Yuri; Woo, Jung Won; Jang, Hak Chul; Sung, Young Chul
Abstract: Aim: To evaluate the pharmacokinetic and pharmacodynamic properties of a novel glycosylated Fc‐fused glucagon‐like peptide‐1(GLP‐1‐gFc) receptor agonist with distinctive receptor binding affinity, designed to improve in vivo stability and safety relative to the commercial GLP‐1 analogue dulaglutide, and assess its safety profile and pharmacokinetics in healthy humans. Materials and Methods: We constructed GLP‐1‐gFc and determined its binding affinity and potency using in vitro instrumental and cell‐based analyses followed by in vivo comparison of the glucose‐lowering and gastrointestinal side effects between GLP‐1‐gFc and dulaglutide. A phase 1 clinical trial was conducted to confirm the efficacy and safety profile of GLP‐1‐gFc. Results: GLP‐1‐gFc showed 10‐fold less binding affinity and 4‐fold less potency than dulaglutide in in vitro. A potency‐adjusted dose delayed HbA1c increase comparable with that of dulaglutide (Change for 6 weeks: 2.4 mg/kg GLP‐1‐gFc, 4.34 ± 0.40 vs. 0.6 mg/kg dulaglutide, 4.26 ± 0.22; n.s.). However, the equivalent efficacy dose and higher dose did not induce malaise‐related responses (blueberry bar consumption, g/mouse: 2.4 mg/kg GLP‐1‐gFc, 0.15% ± 0.03% vs. 0.6 mg/kg dulaglutide, 0.04% ± 0.01%; P < .01) or QT interval changes (mean at 14‐20 hours, mSc: 0.28 mg/kg GLP‐1‐gFc, 0.0‐8.0 vs. 0.07 mg/kg dulaglutide, 8.0‐27.7; n.s.), observed as safety variables in rats and monkeys, compared with those of dulaglutide. Glucose reductions in an oral glucose tolerance test were significant at day 3 postdose without severe gastrointestinal adverse events and pulse rate changes in healthy subjects. Conclusions: These results suggest that GLP‐1‐gFc could be used as a novel GLP‐1 receptor agonist with better safety than dulaglutide to maximize therapeutic benefits in subjects with type 2 diabetes.